2016
DOI: 10.14744/nci.2016.38233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mirtazapine,Gabapentin and Ondansetron to prevent intrathecal morphine induced pruritus

Abstract: OBJECTIVE:Antagonism of the central nervous system inhibitor neurotransmitter gamma-Aminobutyric acid (GABA) or serotonergic system activation is an important factor in the pathogenesis of intrathecal morphine-induced pruritus. This study tested the hypothesis that preoperative use of ondansetron, gabapentin or mirtazapine can prevent morphine-induced pruritus.METHODS:We randomly allocated 80 patients of American Society of Anesthesiology (ASA) classification I and II physical status who were to undergo unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The duration of pruritus was only investigated in the study of Boonmak and colleagues 35 over 48 h, which showed a decline of incidence after 24 h. This is in accordance with other studies. 3 , 73 …”
Section: Discussionmentioning
confidence: 99%
“…The duration of pruritus was only investigated in the study of Boonmak and colleagues 35 over 48 h, which showed a decline of incidence after 24 h. This is in accordance with other studies. 3 , 73 …”
Section: Discussionmentioning
confidence: 99%
“…Preoperative gabapentin (1,200 mg per os ) has been found to significantly delay the onset and reduce the incidence and severity of intrathecal morphine–induced pruritus in patients undergoing orthopedic surgery 162 and prolong the onset of pruritus in patients receiving spinal morphine for unilateral hernia repair. 120 However, a lower dose (600 mg) was not found to significantly decrease the incidence of pruritus compared to placebo and was associated with urinary retention. 163 Further pharmacologic studies in preclinical and clinical models are necessary to characterize the mechanism of action of gabapentin within the nervous system.…”
Section: Treatments For Opioid-induced Pruritusmentioning
confidence: 95%